2020
DOI: 10.32607/actanaturae.10983
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral properties of 1-substituted 3-[ω-(4-oxoquinazolin-4(3h)-yl)alkyl]uracil derivatives

Abstract: А series of uracil derivatives containing a 4-oxoquinazoline fragment bound to the nitrogen atom N3 of the pyrimidine ring by a short methylene bridge was synthesized to search for new antiviral agents. Some compounds in this series are shown to exhibit high inhibitory activity against human cytomegalovirus and the varicella zoster virus in a HEL cell culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…A number of analogues were synthesized to study the structure-antiviral activity dependence. In particular, 1-[5-(4-bromophenoxy)pentyl]-3-benzyl- (22) and -(anthracen-9-ylmethyl)uracil (23) derivatives were obtained by treating uracil 1 with benzyl chloride (20) or 9-(chloromethyl)anthracene (21) in DMF solution in the presence of K 2 CO 3 , the yield of which was 81 and 79%, respectively (Scheme 2). 8) was converted into the target compound 24 with a 77% yield (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of analogues were synthesized to study the structure-antiviral activity dependence. In particular, 1-[5-(4-bromophenoxy)pentyl]-3-benzyl- (22) and -(anthracen-9-ylmethyl)uracil (23) derivatives were obtained by treating uracil 1 with benzyl chloride (20) or 9-(chloromethyl)anthracene (21) in DMF solution in the presence of K 2 CO 3 , the yield of which was 81 and 79%, respectively (Scheme 2). 8) was converted into the target compound 24 with a 77% yield (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…A suspension of 1-[ω-(4-bromophenoxy)alkyl]-uracil derivative 1-7 or 1-[5-(4-bromophenoxy)pentyl]quinazoline-2,4(1H,3H)-dione (25) (1.416 mmol) and freshly calcined potassium carbonate (0.3 g, 2.171 mmol) was incubated in a DMF solution (10 mL) at 80°C for 1 h with stirring, cooled to room temperature, and supplemented with a solution of bromomethylnaphthalene (8)(9)(10)(11), benzyl chloride (20), or 9-(chloromethyl)anthracene ( 21) (1.469 mmol) in DMF (5 mL). The obtained mixture was incubated at that temperature for 24 h with stirring and then evaporated under reduced pressure.…”
Section: General Methods For Obtaining 3-arylmethyl-1-[ω-(bromophenox...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence that resistance to antiviral drugs has become a major ongoing clinical issue. Besides, the discovery of novel molecules to treat viral infections has attracted considerable attention due to the high prevalence of these diseases, the appearance of new viral strains and re-emergence of some viruses, and the limited treatments available. It is worth mentioning that a plethora of research is dedicated toward the synthesis of novel Se derivatives of a wide range of antivirals and the study of their pharmacological activities. …”
Section: Selenized Small Molecule Drugsmentioning
confidence: 99%
“…Paramonova et al [ 45 ] synthesized a set of (ω-p-bromophenoxyalkyl) uracil derivatives with various acetamide moieties. The authors demonstrated that a molecule with a dodecane-1,12-diyl linker ( Figure 3 , 7) has a potent antiviral activity against HCMV.…”
Section: Novel Inhibitors Targeting Viral Proteinsmentioning
confidence: 99%